The Gothic quest - Cram, Ralph Adams (The Baker and Taylor Company, 1907)
On the restoration of idealism (The Knight errant, 1893)--Concerning architectural style (The Architectural review (Boston) 1905)--The Gothic ascendency (Inland architect, 1907)--Meeting-houses or churches (Modern art, 1895)--The development of ecclesiastical architecture in England (The Brickbuilder, 1905)--The development of ecclesiastical architecture in America (The Brickbuilder, 1905)--On the building of churches (Lecture, delivered 1900) The interior decoration of churches (Lecture, delivered 1903) The contemporary architecture of the Roman Catholic church (The Catholic world, 1894)--One of the lost arts (1907)--The case against the École des beaux arts (Lecture, delivered 1896)--Architectural education in the United States (The Magazine of Christian art, 1907)